A 14-year dataset of in situ glacier surface velocities for a tidewater and a land-terminating glacier in Livingston Island, Antarctica - Machio, Francisco; Rodríguez-Cielos, Ricardo; Navarro, Francisco; Lapazaran, Javier; Otero, Jaime (Earth System Science Data, 2017)
We present a 14-year record of in situ glacier surface velocities determined by repeated global navigation satellite system (GNSS) measurements in a dense network of 52 stakes distributed across two glaciers, Johnsons (tidewater) and Hurd (land-terminating), located on Livingston Island, South Shetland Islands, Antarctica. The measurements cover the time period 2000-2013 and were collected at the beginning and end of each austral summer season. A second-degree polynomial approximation is fitted to each stake position, which allows estimating the approximate positions and associated velocities at intermediate times. This dataset is useful as input data for numerical models of glacier dynamics or for the calibration and validation of remotely sensed velocities for a region where very scarce in situ glacier surface velocity measurements have been available so far.
Keywords: JCR; Scopus